Corporate social responsibility, job satisfaction, and customer orientation in Angola - Duarte, A. P.; Neves, J. G.; Gomes, D. R.; Moisés, G. A. (World Review of Entrepreneurship, Management and Sustainable Development, 2019)
This study sought to examine the effect of corporate social responsibility (CSR) on employees' costumer orientation through the mediating role of job satisfaction for a sample of tourism and hospitality employees in Angola. Data were collected from 125 respondents using anonymously completed structured questionnaires. Perceived CSR was assessed by the scale developed by Martínez et al. (2013), which includes social, economic and environmental issues. Job satisfaction was measured using Lima et al.'s (1994) job-facet scale, while customer orientation was evaluated using a reduced version of Saxe and Weitz's (1982) customer-orientation scale. The three dimensions of CSR in question have dissimilar levels of association with customer orientation. Only perceptions of company engagement in social CSR practices explain employees' customer orientation, and the relationship is partially mediated by job satisfaction. Additional studies with larger samples and longitudinal designs are needed to determine further the influence of CSR on employees' job satisfaction and customer orientation.